When do we become adults? Review of theory, research and recent advances from an interdisciplinary perspective - Knežević, Martina, psihologinja (2018)
Major developmental psychology theories, such as psychoanalytic, behavioural or cognitive, have tried to explain how people grow and change over the course of a lifetime. These theories have mainly focused on the stages of development early in life - from infancy to adolescence - leaving the impression that after adolescence no significant leaps in development occur. However, a large body of evidence that has emerged recently revealed that becoming an adult is much more complicated and temporally extended than previously believed. The aim of this paper was to use an interdisciplinary approach to tap into the issue of transition to adulthood by integrating recent brain and cognitive maturational findings from neuroscience and cognitive psychology while considering traditional and legal markers of adulthood. We first discuss some of the questions related to definitions of the period of adulthood through societal and legal frameworks. Next, we examine some of the prevailing views on protracted structural and functional brain maturation and its impact on cognitive development, emphasizing the need and the potential value of investigating how these changes may influence important life choices during early young adulthood that have long-lasting consequences. Finally, based on evidence from existing research, we highlight the importance of deeper appreciation and integration of findings from different research disciplines in order to better understand strengths and vulnerabilities of young adults.
Numerosas teorías de la psicología de desarrollo, como la teoría psicoanalítica, conductual o cognitivista, han tratado de explicar cómo la gente madura y cambia durante la vida. Estas teorías se han enfocado en etapas tempranas de vida – desde la niñez hasta la adolescencia – dejando la impresión que después de la adolescencia no hay saltos significativos en el desarrollo. Sin embargo, las investigaciones del desarrollo humano en los últimos veinte años han demostrado que la maduración es un proceso mucho más complejo y duradero de lo que se suponía antes. El objetivo de este trabajo fue, a través de un enfoque interdisciplinario, investigar la transición a la edad adulta a través de los resultados recientes de las investigaciones en el campo de neurociencia y psicología cognitiva sobre la maduración del cerebro y las habilidades cognitivas, a la vez teniendo en cuenta los límites tradicionales y legislativos de la edad adulta. En la primera parte del trabajo se discute sobre ciertas cuestiones relacionadas con cómo definir la edad adulta a través de los marcos sociales y legales. Luego investigamos en qué modo la maduración estructural y funcional prolongada del cerebro influye en las habilidades cognitivas, acentuando la necesidad y el valor de investigaciones del modo en el que estos cambios pueden influir en la toma de decisiones importantes durante la edad adulta temprana, y que pueden tener consecuencias a largo plazo. En fin, a base de las pruebas de investigaciones existentes, acentuamos la importancia de aceptar e integrar los hallazgos de diferentes disciplinas de investigación para entender mejor las fuerzas y la vulnerabilidad de personas jóvenes que están a punto de pasar a la edad adulta.
Brojne su teorije razvojne psihologije, poput psihoanalitičke, biheviorističke ili kognitivističke, pokušale objasniti kako ljudi sazrijevaju i mijenjaju se tijekom života. Ove su teorije usmjerene na rane životne faze – od djetinjstva do adolescencije – ostavljajući dojam kako nakon adolescencije ne dolazi do značajnijih skokova u razvoju. Međutim, istraživanja su ljudskog razvoja u posljednjih 20-ak godina pokazala kako je sazrijevanje puno složenije te vremenski dugotrajnije nego se prethodno smatralo. Cilj je ovoga pregleda bio interdisciplinarnim pristupom istražiti pitanje prijelaza u odraslu dob prikazom najnovijih rezultata istraživanja o sazrijevanju mozga i kognitivnih sposobnosti iz područja neuroznanosti i kognitivne psihologije istovremeno razmatrajući tradicionalne i zakonom određene granice odraslosti. U prvom se dijelu rada raspravlja o određenim pitanjima vezanim uz definiranje razdoblja odraslosti kroz društvene i pravne okvire. Zatim se navodi kako produljeno strukturalno i funkcionalno sazrijevanje mozga utječe na kognitivne sposobnosti, naglašavajući potrebu i vrijednost istraživanja načinā na koje ove promjene mogu utjecati na donošenje važnih odluka tijekom rane odrasle dobi, a koje mogu imati dalekosežne posljedice. Konačno, na temelju se dokaza iz postojećih istraživanja ističe važnost prihvaćanja i integriranja nalaza iz različitih istraživačkih disciplina kako bi se bolje razumjela snaga i ranjivosti mladih osoba na pragu odrasle dobi.
Bibliografija: str. 283-288.
Sažetak ; Resumen
Keywords: Sazrijevanje -- Adolescencija -- Odrasle osobe -- Kognitivne sposobnosti -- Razvoj mozga -- Interdisciplinarni pristup